Functional and biochemical characterization of human eukaryotic translation initiation factor 3 in living cells - Wagner, Susan; Herrmannová, Anna; Malík, Radek; Peclinovská, Lucie; Valášek, Leoš Shivaya (Molecular and cellular biology, 2014)
The main role of the translation initiation factor 3 (eIF3) is to orchestrate formation of 43S-48S preinitiation complexes (PICs). Until now, most of our knowledge on eIF3 functional contribution to regulation of gene expression comes from yeast studies. Hence, here we developed several novel in vivo assays to monitor the integrity of the 13-subunit human eIF3 complex, defects in assembly of 43S PICs, efficiency of mRNA recruitment, and postassembly events such as AUG recognition. We knocked down expression of the PCI domain-containing eIF3c and eIF3a subunits and of eIF3j in human HeLa and HEK293 cells and analyzed the functional consequences. Whereas eIF3j downregulation had barely any effect and eIF3a knockdown disintegrated the entire eIF3 complex, eIF3c knockdown produced a separate assembly of the a, b, g, and i subunits (closely resembling the yeast evolutionary conserved eIF3 core), which preserved relatively high 40S binding affinity and an ability to promote mRNA recruitment to 40S subunits and displayed defects in AUG recognition. Both eIF3c and eIF3a knockdowns also severely reduced protein but not mRNA levels of many other eIF3 subunits and indeed shut off translation. We propose that eIF3a and eIF3c control abundance and assembly of the entire eIF3 and thus represent its crucial scaffolding elements critically required for formation of PICs.
Keywords: HeLa Cells; proliferace buněk; RNA ribozomální; buněčné linie; HEK293 Cells; eukaryotický iniciační faktor 3; vazba proteinů; proteiny vázající RNA; lidé; HeLa buňky; malá interferující RNA; ribozomální proteiny; HEK293 buňky; Cell Line; RNA, Ribosomal; regulace genové exprese; iniciace translace peptidového řetězce; RNA, Small Interfering; Cell Proliferation; Eukaryotic Initiation Factor-3; RNA Interference; RNA-Binding Proteins; Ribosomal Proteins; Gene Expression Regulation; RNA interference; Protein Binding; Peptide Chain Initiation, Translational; Humans